Interview: Between the local productive arrangement and the industrial pharmaceutical market: setbacks of the public supply of herbal medicines in Ribeirão Preto - Carlessi, Pedro Crepaldi; Silva, Katellyn Costa [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
In this interview, Lúcia Helena Terenciani Rodrigues Pereira presents the itinerary followed by Ribeirão Preto/SP when implementing the supply of herbal medicines in the municipality.
Entrevista: Entre o arranjo produtivo local e o mercado farmacêutico industrial: contrariedades da oferta pública de fitoterápicos em Ribeirão Preto
Keywords: Health System; Herbal medicine; Medicinal plants